The Mechanical Properties of Water-Based Emulsion Polymers: Effect of Reaction Conditions - Sarac, Ayfer; Turhan, Kadir (SPRINGER, 2009)
Emulsion homopolymers and copolymers (latexes) are widely used in architectural interior and exterior paints, adhesives, and textile industries. Colloidal stabilizators in the emulsion polymerization strongly affect not only the colloidal properties of latexes but also the film and mechanical properties, in general. Additionally, the properties of polymer/copolymer latexes depend oil the copolymer composition, polymer morphology, initiator, polymerization medium and colloidal characteristics of copolymer particles. Copolymerization of vinyl acetate with acrylic monomers can lead to the production of latex having a wide range of mechanical and molecular properties depending on the molecular structure of the emulsifier, and also above parameters. In this study, mechanical properties of emulsion copolymers of vinyl acetate and butyl acrylate, which consisted of a nonionic emulsifier (30 mol ethoxylated nonylphenol), an oligomeric stabilizator, and ammonium persulfate or potassium persulfate as initiators by changing monomer ratios from 90:10 to 10:90 for VAc:BuA, were determined by differential scanning calorimeter.
Keywords: Copolymers; differential scanning calorimeter; emulsion homopolymers; latexes; oligomeric stabilizator; polymerization; VINYL-ACETATE; Biochemistry & Molecular Biology; Chemistry